PAIN MANAGEMENT IN THE EMERGENCY DEPARTMENT - A LITERATURE REVIEW - Michał Szalach,; Aleksandra Żywicka,; Zuzanna Rabczak,; Marcin Narloch,; Kamila Mozga,; Mateusz Jasiński,; Małgorzata Kuczek,; Jakub Rusek,; Justyna Tasior,; Bartosz Burda, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Pain is the most common presenting symptom in emergency departments and requires timely, accurate assessment and effective management to prevent complications and improve patient outcomes. This review focuses on the mechanisms, classification, and management strategies for acute pain in the ED, including common clinical presentations and evidence-based therapeutic approaches.Materials and methods: A literature search was conducted in the PubMed database to find recent systematic reviews and meta-analyses on pain management in emergency medicine. Keywords included: pain, analgesics, emergency department, injury.Results: A review of the literature indicates that pain management in emergency medicine is primarily guided by the type, cause, and severity of pain. A multimodal approach offers significant therapeutic benefits. Despite local differences in drug preferences and clinical guidelines, accurate pain assessment and the prompt, appropriate adjustment of analgesics to symptom intensity remain a fundamental principle of pain management. Equally important is the use of adjuvant therapies and non-pharmacological interventions, including psychological support, individualized care and effective communication with the patient.Conclusion: Effective pain management in emergency settings requires a structured, patient-centered, and interdisciplinary approach. Incorporating both pharmacologic and supportive strategies not only enhances acute symptom relief but also contributes to better long-term outcomes and healthcare resource utilization.